2017
DOI: 10.5812/archneurosci.14553
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Congruity Between Tumor Consistency in Pituitary Macroadenomas and Preoperative Diffusion Weighted Imaging and Apparent Diffusion Coefficient (ADC) Map?

Abstract: Background: Pituitary adenomas are the most common space-occupying lesions in the sellar region. Pituitary adenomas are usually soft, but 5 to 13% of macroadenomas are fibrous. The resection of firm tumors by curettage or suction is challenging. Therefore, preoperative knowledge of the pituitary adenomas consistency could help neurosurgeons plan more appropriate surgical procedures. In this regard, predicting fibrous adenomas by magnetic resonance imaging (MRI) is typically difficult and the results are contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Tumors with hard consistency were initially associated with higher ADC values when compared to pituitary adenomas that were easily aspirated [15,[26][27][28]]. However, confronting results have emerged over the years [14,19,25,29,30], with most studies currently demonstrating instead an association between lower ADC values and hard consistency [29,[31][32][33].…”
Section: Diffusion Imaging/apparent Diffusion Coe Cientmentioning
confidence: 99%
“…Tumors with hard consistency were initially associated with higher ADC values when compared to pituitary adenomas that were easily aspirated [15,[26][27][28]]. However, confronting results have emerged over the years [14,19,25,29,30], with most studies currently demonstrating instead an association between lower ADC values and hard consistency [29,[31][32][33].…”
Section: Diffusion Imaging/apparent Diffusion Coe Cientmentioning
confidence: 99%
“…Tumors with hard consistency initially had higher ADC values than pituitary adenomas that were easily aspirated [14,[25][26][27]. However, over the years, contradictory results have surfaced [13,18,24,28,29], with the majority of studies nding a link between lower ADC values and hard consistency [28,[30][31][32]. Lower ADC levels have also been linked to a higher risk of early progression/recurrence, cavernous sinus invasion, failed chiasmatic decompression, and greater tumor height and volume [29,33,34].…”
Section: Diffusion Imaging/apparent Diffusion Coe Cientmentioning
confidence: 99%
“…The role of ECM molecules in controlling the biophysical properties of the stroma (such as molecular density, topography, rigidity/stiffness, and tension) may also prove relevant for pituitary tumors since it has already been shown that characteristics such as tissue stiffness (which usually increases in malignant tissues) play a major role in other cancers [79,101,102,103]. In the pituitary field, our knowledge of pituitary tumor stiffness is rather limited and has mainly been assessed from a surgical point of view (i.e., the preoperative predictive value of different imaging techniques), as firm fibrous tumors, representing <20% of the resected pituitary tumors, are more difficult to resect through a transsphenoidal approach than the soft tumors, which represent the majority of pituitary tumors [104,105,106,107,108]. The assessment of tumor collagen content, as evaluated by Masson’s staining, has shown that the consistency of the tumor as evaluated by the surgeon was associated with the collagen content, with firm tumors having more collagen [105,106,107].…”
Section: Composition and Remodeling Of The Extracellular Matrix Inmentioning
confidence: 99%
“…In the pituitary field, our knowledge of pituitary tumor stiffness is rather limited and has mainly been assessed from a surgical point of view (i.e., the preoperative predictive value of different imaging techniques), as firm fibrous tumors, representing <20% of the resected pituitary tumors, are more difficult to resect through a transsphenoidal approach than the soft tumors, which represent the majority of pituitary tumors [104,105,106,107,108]. The assessment of tumor collagen content, as evaluated by Masson’s staining, has shown that the consistency of the tumor as evaluated by the surgeon was associated with the collagen content, with firm tumors having more collagen [105,106,107]. While statistical analysis associating tumor consistency and the invasion of the cavernous sinus did not show significant differences between soft and firm tumors in a series of 34 pituitary tumors [107], it would appear important to assess clinico-pathological associations in larger series and also to more precisely map the actual stiffness landscape of those tumors through atomic force microscopy (AFM), as has already been done for normal anterior pituitary tissue [109].…”
Section: Composition and Remodeling Of The Extracellular Matrix Inmentioning
confidence: 99%